A Technology-Aided Program to Support Basic Occupational Engagement and Mobility in Persons with Multiple Disabilities - Lancioni, Giulio E.; Singh, Nirbhay N.; O’Reilly, Mark F.; Sigafoos, Jeff; Alberti, Gloria; Campodonico, Francesca; Perilli, Viviana; Chiariello, Valeria; Zimbaro, Carmen (Frontiers in Public Health, 2017)
Background: Persons with severe/profound intellectual and multiple disabilities tend to be passive and sedentary. Promoting their occupational engagement and mobility (i.e., indoor walking) can help modify their condition and improve their environmental input, health, and social image. Aim: This study assessed whether a technology-aided program was suitable to (a) support independent occupation and mobility in eight participants with intellectual and sensory disabilities and (b) eventually increase the participants’ heart rates to levels considered beneficial for them. Method: The program, which involved a computer system regulating the presentation of auditory or visual cues and the delivery of preferred stimulation, was introduced according to a non-concurrent multiple baseline design across participants. The auditory or visual cues guided the participants to collect objects from different desks and to transport them to a final destination (i.e., depositing them into a carton). Preferred stimulation was available to the participants for collecting and for depositing the objects. Results: During the program, all participants had increases in their independent responses of collecting objects and transporting them to the final destination. Their heart rates also increased to levels reflecting moderate-intensity physical exercise, potentially beneficial for their health. Conclusion: A program, such as that used in this study, can promote occupational engagement and mobility in persons with multiple disabilities.